Mixed Neuroendocrine Tumor of the Common Bile Duct - Linder, Revital; Dorfman, Tatiana; Ben-Ishay, Offir; Kakiashvili, Eli; Velodavsky, Eugene; Kluger, Yoram (JOP. Journal of the Pancreas, 2013)
Context Mixed adenoendocrine tumors of the extrahepatic bile ducts are exceedingly rare and most of those who are rarely diagnosed are adenocarcinomas. Neuroendorine tumors accounts for only 0.2-2%. Case report We report a case of mixed adenoneuroendo-carcinoma of the common bile duct in an 82-year-old male. Conclusion Clinical experience suggests that the neuroendocrine component of mixed tumors behave more aggressively than the regular biliary adenocarcinoma component. This clinical behavior may have an important role in the management of this clinical entity. Image: Mixture of usual cholangiocarcinoma and small cell neuroendocrine carcinoma.